Revision of the Therates fruhstorferi complex (Coleoptera, Cicindelidae) - Matalin, Andrey V.; Wiesner, Jürgen (Zootaxa, 2023)
The taxonomic structure of the Therates fruhstorferi species complex (sensu lato) within the batesi-species group is revised. The lectotypes and paralectotypes of Therates fruhstorferi W. Horn, 1902 and Therates fruhstorferi sauteri W. Horn, 1912 are designated. Therates biserratus Tan, Mo, Liang, 1991 and T. vitalisi ida Mandl, 1954 are restored from the synonyms of T. vitalisi W. Horn, 1913 as the separate species and subspecies, respectively while T. sauteri is considered as a separate species, but not as a subspecies of T. fruhstorferi. Three species and two subspecies are described as new: T. fruhstorferi australis ssp. n.—from southern Vietnam; T. pseudovitalisi sp. n.—from northern Laos; T. pseudovitalisi tibetana ssp. n.—from eastern Tibet, China; T. hunanensis sp. n.—from the Chinese Province Hunan; T. ziyardamensis sp. n.—from northern Myanmar. An identification key and distribution map of the species of Therates fruhstorferi complex are provided.